Reoperative pediatric surgery - Teich, Steven A. (Humana Press, 2008)
Reoperative surgery is a prevailing challenge faced by pediatric surgeons. Reoperative Pediatric Surgery constitutes in one volume the most up to date information and techniques for critical cases in all of the pediatric surgical specialties including oncology, gastroenterology, gynecology, urology, radiology, and cardiology. Recognized experts impart their knowledge of indications for reoperative surgeries, radiologic evaluation, surgical procedures which may require seldom used and extremely complex techniques, and the risks and outcomes of these specialized approaches. These practicing surgeons provide insight into intricate corrective procedures involving the placement of grafts, stents, and supports with necessary forecasting for complications arising from anatomic growth and disease recurrence. This comprehensive book is an indispensable resource covering the full spectrum of pediatric reoperation addressing the complications of common pediatric surgeries including congenital defect repair, chest wall repair, orchiopexy, hernia repair, fundoplication, and placement of vertriculoperitoneal shunts as well as unique cases of tumor excision and reoperative oncology. With its detailed masterful approach and full color photographs, Reoperative Pediatric Surgery is the gold-standard for this multi-faceted discipline. Radiology of the postoperative patient -- Techniques for difficult venous and arterial access -- Reoperative head and neck surgery -- Reoperative thyroid and parathyroid surgery -- Complications of pectus excavatum and carinatum repair -- Complications of CDH repair and recurrent CDH -- Reoperation for Jeune's syndrome -- Reoperation for benign breast disorder -- Abdominal wall disruption -- Reoperation after esophageal atresia repair and other esophageal conditions -- Reoperation after failed fundoplication and other gastric operations -- Reoperation after duodenal atresia repair and management of duodenal fistulas -- Reoperation after surgery of the small bowel -- Interventions for appendiceal complications -- Reoperation for inflammatory bowel disease -- Reoperation for stoma complications -- Reoperative surgery for hirschsprung disease -- Reoperative surgery for anorectal malformations -- Reoperation for recurrent anal and perianal conditions -- Reoperation of the liver and biliary system -- Reoperation of the pancreas -- Rhabdomyosarcoma -- Neuroblastoma -- Wilms’ tumor -- Peripheral neuroectodermal tumors -- Osteosarcoma metastases -- Neurofibromatosis -- Tumors of the liver -- Sacrococcygeal teratoma -- Recurrent hernia, hydrocele, and varicocele -- Failed orchidopexy and complications of circumcision -- Complications of vaginoplasty and clitoroplasty -- Abdominal complications of ventricular-peritoneal shunts -- Revisional bariatric surgery in adolescents.